(untitled) (KYAMC Journal, 2017)
Background: Food supply at national level is satisfactory in Bangladesh though per capita energy intake and diversity of food are important concerns with food security in rural areas. Objectives: This nutritional survey was carried out to observe the food diversity at household level and to estimate per capita energy intake in rural areas for assessing the existing situation. Methodology: A total 648 households were surveyed in three villages selected by cluster sampling technique. Informations were collected on the basis of 24 hours’ recall of respondents about the food items and the amount consumed at the household on the previous day and eating occasions by structured partially close ended questionnaire. Results: Food diversity was on the ’Border line’ (3-6 score) at 65.28% of the household. Rice and oil were consumed at every house but per capita intake of meat, fish, fruits and vegetables were 64.67, 62.07, 20.11 and 57.78 gram respectively where those were consumed. Per capita food energy intake per day was 2695 kcal from 150.45 gram (616.85 k cal) of protein, 397.50 gram (1590.01 k cal) of carbohydrate and 52.49 gram (488.13 k cal) of fat from all sources giving 22.89%, 59.00 % and 18.11% of the dietary energy respectively. Interpretation & Conclusion: Diversity of foods and consumption of animal protein, vegetables and fruits intake were lower in amount. Recommendation: Recommendation was made to initiate health education program for inclusion of varieties of food and increase daily consumption of animal protein, fruits and vegetables. KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 687-690